2009
DOI: 10.1097/shk.0b013e318193e187
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation and Vascular Reactivity During Endotoxemia and Endotoxin Tolerance in Humans

Abstract: The purpose of the study was to investigate microcirculation and vascular reactivity during experimental endotoxemia and endotoxin tolerance in humans by comparing different methods of approach. Endotoxin tolerance was induced in nine healthy volunteers by intravenous injection of 2 ng . kg(-1) . d(-1) LPS for 5 consecutive days. Microcirculation and vascular reactivity were monitored before and after LPS administrations on days 1 and 5 by near-infrared spectroscopy, sidestream dark-field imaging, and forearm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…These alterations can be observed very early in the course of sepsis, even within a few hours of hospital admission [57,101]. Similar alterations, of lower magnitude, can be induced by low-dose endotoxin administration in healthy volunteers [102].…”
Section: Severe Sepsis and Septic Shockmentioning
confidence: 74%
“…These alterations can be observed very early in the course of sepsis, even within a few hours of hospital admission [57,101]. Similar alterations, of lower magnitude, can be induced by low-dose endotoxin administration in healthy volunteers [102].…”
Section: Severe Sepsis and Septic Shockmentioning
confidence: 74%
“…It is assumed that the higher the StO 2 recovery slope, the greater the reactive hyperaemia capacities. A recent study reported a 79% decrease in StO 2 recovery slope after an endotoxin challenge in healthy [26]. Accordingly, Creteur et al showed that the StO 2 recovery slope was lower (1) in septic patients than in other categories of patients and in volunteers, (2) in septic patients with shock than without, and (3) in nonsurvivors than in survivors [17].…”
Section: Discussionmentioning
confidence: 99%
“…dysfunction [24], among other mechanisms by activating the endothelium through a receptor complex consisting of TLR4, CD14 and myeloid differentiation (MD)-2 [25], and by inducing apoptosis of endothelial cells [26]. Endothelial dysfunction and impaired arterial elasticity are present throughout the atherosclerotic process [27], and an association of LPS with carotid atherosclerosis has been described in the general population [28] as well as in HIV-infected individuals [29].…”
Section: Figmentioning
confidence: 99%